Revolução de caranguejos: políticas para o teatro no Espírito Santo durante a ditadura militar - Cid, Duílio Henrique Kuster (2013)
The objective of this dissertation was to investigate policies for theater developed in Espírito Santo during the Military Dictatorship. In this sense, I worked, methodologically, with different scales of research, analyzing evidence from capixabas theater artists who experienced the period and management reports from cultural institution responsible for scheduling and executing the cultural policy of the state, the Fundação Cultural do Espírito Santo (FCES), as well as seeking to understand the process of development of cultural policies that occurred at the federal level. Thus, in particular, chose to highlight the seemingly contradictory aspect of the regime installed after the coup of 1964, which was also responsible for chasing and arresting many artists and prohibit countless works. I made a time frame that runs from the date of the coup until 1980 and was able to identify three distinct moments of the relationship between state and theater activity in Espírito Santo: 1) from 1964 to 1969, a period of lack of investment in the sector; 2) 1970 to 1977, with the development of a large number of cultural actions and 3) from 1977 to 1980, with the reduction of investments that had been held so far, culminating in the extinction of FCES. Based on the concept of teatrocracia of George Balandier, interpreted that the oscillations observed in these three moments were related to the image that the bionic state governors sought to convey to the people themselves.